Mathematical Modeling and Simulation of Robotic Dynamic Systems - Mammadova, K.A. (Herald of Azerbaijan Engineering Academy, 2022)
The mathematical model of the robot generally consists of a nonlinear multi-link system, so various simplifications are used in the analysis of its properties. In particular, linear models of robots and control systems are commonly used to study the controllability and robustness of robots. In this case, linear models are built on the edges of the actions of the robot or system, the properties of which must be studied. Therefore, in order to build linear models of a robot and its control system, it is first necessary to find the fixed equations of a particular robot, as well as its control system as a whole. In this work, the procedure for developing a mathematical description of the robot is given. A three-dimensional model is developed, its main characteristics are determined. A description of SolidWorks is provided to develop a three-dimensional model. The model is developed in the form of a system of differential and algebraic equations. Aerodynamic research of the model, analysis of stability and handling are carried out.